High Rate of Fatal Overdose After Release from Prison In BC, Canada: A Data Linkage Study - Stuart A Kinner; Wenqi Gan; Amanda Slaunwhite (International Journal of Population Data Science, 2020)
Introduction The province of BC, Canada is in the grips of a sustained overdose epidemic. People released from prison are at increased risk of fatal drug overdose, but the impact of the overdose epidemic on mortality after release from prison in BC is poorly understood. Few studies have been able to examine risk factors for overdose death in this population.